Divergent dielectric characteristics in cascaded high-K gate stacks with reverse gradient bandgap structures. (26th May 2016) - Tsai, Meng-Chen; Cheng, Po-Hsien; Lee, Min-Hung; Lin, Hsin-Chih; Chen, Miin-Jang
Abstract: The characteristics of cascaded high- K gate stacks with reverse dielectric sequence, TiO2 /ZrO2 /Al2 O3 and Al2 O3 /ZrO2 / TiO2, on the Si substrate were investigated. The reverse sequence with different gradient bandgap structure gives rise to distinct conduction pathways, resulting in significant divergence of the leakage current density ( J g ) and the capacitance equivalent thickness (CET). The trapping sites in the high-permittivity TiO2 layer dominate the leakage current paths and strongly impact the conductance and the capacitance of the cascaded high- K gate stacks. Thus, a low CET of 1.05 nm and a low J g of ∼5  ×  10 –4 A cm −2 were achieved due to effective suppression of the leakage current through the traps of TiO2 in the cascaded TiO2 /ZrO2 /Al2 O3 gate stack. In addition, the TiO2 layer gets crystallized in the cascaded TiO2 /ZrO2 /Al2 O3 structure to achieve a higher capacitance because of the intermixing between TiO2 and ZrO2 due to the different reactivity of the precursors for Ti and Zr. This study demonstrates a way to effectively incorporate the high permittivity and low-bandgap materials, such as TiO2, into high- K gate stacks, to further improve device scaling.